Rethinking the Expanded Public Works Programme for sustainable income generation in South Africa: insights from Duncan Village - Moto, Babongile; Hamunakwadi, Purity; Mbanga, Sijekula (Frontiers in Sustainable Resource Management, 2025)
BackgroundExpanded Public Works Programmes (EPWPs) in South Africa aim to tackle unemployment and poverty, particularly in informal settlements, by offering temporary employment and skills development. Despite more than a decade of implementation, concerns remain about their long-term impact on sustainable income generation and community development.MethodsThis study adopted an interpretivist research design, using qualitative methods to investigate the effectiveness of EPWPs in Duncan Village, an informal settlement in the Buffalo City Metropolitan Municipality. Data was collected through in-depth interviews with five key informants from the Department of Public Works and local government, alongside four focus group discussions involving 40 EPWP beneficiaries. A thematic analysis approach was applied, complemented by a comprehensive literature review to contextualize findings.FindingsThe findings revealed that EPWPs contribute to short-term employment, improved self-worth, and basic skills development. However, the programmes are hindered by coordination challenges, inadequate administrative support, and misalignment between skills training and local labor market needs. Participants emphasized the necessity of accredited training, access to microfinance, and stronger interdepartmental collaboration to support long-term livelihood strategies.ConclusionsEPWPs play a valuable role in providing immediate relief to vulnerable communities, but their transformative potential remains limited without structural improvements. To increase their impact, policy interventions should prioritize sustainable skills development, improve administrative coordination, and enhance post-programme support mechanisms to foster entrepreneurship and long-term employment. These findings contribute to the growing body of international literature on public employment programmes, drawing parallels with similar initiatives such as India's MGNREGA and Brazil's Bolsa Família.